A qualitative descriptive study exploring clinicians' perspectives of the management of older trauma care in rural Australia - Noha Ferrah; Catriona Parker; Joseph Ibrahim; Belinda Gabbe; Peter Cameron (BMC, 2023)
Abstract Background For older trauma patients who sustain trauma in rural areas, the risk of adverse outcomes associated with advancing age, is compounded by the challenges encountered in rural healthcare such as geographic isolation, lack of resources, and accessibility. Little is known of the experience and challenges faced by rural clinicians who manage trauma in older adults. An understanding of stakeholders' views is paramount to the effective development and implementation of a trauma system inclusive of rural communities. The aim of this descriptive qualitative study was to explore the perspectives of clinicians who provide care to older trauma patients in rural settings. Method We conducted semi-structured interviews of health professionals (medical doctors, nurses, paramedics, and allied health professionals) who provide care to older trauma patients in rural Queensland, Australia. A thematic analysis consisting of both inductive and deductive coding approaches, was used to identify and develop themes from interviews. Results Fifteen participants took part in the interviews. Three key themes were identified: enablers of trauma care, barriers, and changes to improve trauma care of older people. The resilience of rural residents, and breadth of experience of rural clinicians were strengths identified by participants. The perceived systemic lack of resources, both material and in the workforce, and fragmentation of the health system across the state were barriers to the provision of trauma care to older rural patients. Some changes proposed by participants included tailored education programs that would be taught in rural centres, a dedicated case coordinator for older trauma patients from rural areas, and a centralised system designed to streamline the management of older trauma patients coming from rural regions. Conclusions Rural clinicians are important stakeholders who should be included in discussions on adapting trauma guidelines to the rural setting. In this study, participants formulated pertinent and concrete recommendations that should be weighed against the current evidence, and tested in rural centres.